‘FROM SAND TRAY TO SOUL BIRD’ - McQuade, Anna (2007)
During my development and clinical practice particularly this year, I have been fortunate enough to have been able to expand my working knowledge of counselling children and young people. In all of my writings to press, I have endeavoured to write in such a way that I believe has allowed me to share my experiences, as me and of the children that I have honoured in my work, as them. Not as someone that I profess to be, but as someone who has written from the heart in describing her increasing passion in her work and of her experiences with troubled young people.